Greece in Antarctica: Exploring Novel Routes to Polar Engagement - Tsiouvalas, Apostolos; Dimitrakopoulos, Nikolaos (HAPSc Policy Briefs Series, 2024)
Over the last few years, Antarctica has attracted the interest of a significantly increasing number of both state and non-state actors, serving as a physical and political arena that hosts a unique combination of socio-ecological developments. Ranging from the ongoing battle against climate change to more complex geopolitical and economic antagonisms arising from resource extraction and fishing, the frozen continent will undoubtedly enter mainstream political discourse with increased force in the coming years. This policy brief aims to explore Greece’s developing relationship with Antarctica, building on the momentum of the first-ever official Greek expedition to the continent. After examining the status quo of established Greek-Antarctic relations, this brief attempts to decode the motives behind the recent intensification of Greece’s Antarctic engagement, while also exploring proposals that could promote Greek geostrategic interests in the region.